DICTION AND IDEOLOGY OF KAESANG PANGAREP'S FIRST SPEECH IN A POLITICAL FORUM - Dian Ardiansah; Saifullah, Aceng Ruhendi (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
This study aims to analyze the diction, language power, and ideology used by Kaesang Pangerep in his first political speech. The analysis was based on Fairclough's CDA theory (1989) and combined with Thomas N. Huckin's model. The research method used was descriptive qualitative, focusing on elaborating paragraphs, sentences, and words. The analysis began with an examination of the entire text, followed by a more detailed analysis of sentences and words. The text was analyzed to understand the contextual interpretation of the relationship between language power and ideology. Additionally, language relevance and style features were analyzed to understand Kaesang Pangarep's diction in his public speech. The results indicated that the connections between language power and ideology were broadly defined through CDA. The study revealed that although there were instances of irrelevant language use, Kaesang Pangarep's speech was directly aimed at the Millennial party. The linguistic ideology in his speech was observed to reflect a legacy role from current political issues, suggesting a shift in the language used to build the ideology, with specific aims and a legacy of current linguistic issues.